Vulnerability to alcohol consumption, spiritual transcendence and psychosocial well-being: test of a theory - Luz Patricia Díaz Heredia; Alba Idaly Muñoz Sanchez (Universidade de São Paulo, 2016)
Abstract Objective: to demonstrate the relations among vulnerability, self-transcendence and well-being in the young adult population and the effect of each of these variables on the adoption of low-risk consumption conducts. Method: quantitative and cross-sectional correlation study using structural equations analysis to test the relation among the variables. Results: an inverse relation was evidenced between vulnerability to alcohol consumption and spiritual transcendence (β-0.123, p 0.025) and a direct positive relation between spiritual transcendence and psychosocial well-being (β 0.482, p 0.000). Conclusions: the relations among the variables spiritual transcendence, vulnerability to alcohol consumption and psychosocial well-being, based on Reed's Theory, are confirmed in the population group of young college students, concluding that psychosocial well-being can be achieved when spiritual transcendence is enhanced, as the vulnerability to alcohol consumption drops.